Assessing infant and young child feeding priorities to inform the development of a nutrition social and behaviour change communication (SBCC) strategy during a pandemic threat. Issue 3 (30th September 2022) - Turk, T; Poonawala, A; Shulman, S; Sepoloane, P
Abstract : Objectives: This study was undertaken to identify stakeholder needs and wants in relation to an Infant and Young Child Feeding, Social and Behaviour Change Communication (SBCC) strategy for the 16 Southern African Development Community (SADC) member states during Covid-19 lockdowns and travel restrictions. Design: A rapid-assessment mixed-methods approach using qualitative and quantitative studies was adopted. Secondary data sources supported in-field findings. Setting/Subjects: Qualitative approaches included 17 key informant interviews from 7 SADC member states. Quantitative methods of an online survey elicited feedback from 61 participants from 11 SADC member states. Outcome measures: More strategic, best practice, infant and young child feeding SBCC programmes are recommended in SADC. Results: Programme challenges included increased demands on health systems from Covid-19, poor attitudes and beliefs toward IYCF behaviours, the dual burden of undernutrition and overnutrition, and financial and human resource capacity challenges to implement and evaluate SBCC campaigns at scale. Opportunities were also identified for improved detection, better meeting IYCF nutritional needs from locally sourced foods, training and capacity building for greater engagement of front-line field staff, effective policy development to support parent-friendly hospitals and workplaces, and improved regional integration. Conclusions: The needs assessment demonstrated that priority programme planning can continue while the health sector deals with a pandemic threat. The adaptation to virtual support provided a variety of learnings for research designs, data collection and analysis, albeit over an extended timeframe of six months. A number of innovative approaches were identified in the resultant SBCC strategy for SADC along with opportunities for regional efficiencies in adapting existing, best practice SBCC creative and programming approaches.